A rights-based approach to foreign agro-investment governance in Cameroon, Uganda and South Africa - Ashukem, Jean-Claude Nkwanyuo (North-West University, 2016)
The practice of foreign agro-investment (FAI) for the production of food crops and biofuel crops has been a recent phenomenon in sub-Saharan Africa and other developing countries. In fact, the present era of climate change has caused foreign countries to acquire vast tracts of land - often through multinational corporations - in order to propagate biofuel or expand their home industries abroad. Practices of FAI have resulted in a form of land grabbing, as local communities are often evicted from their land without their consent. FAI activities are reported to have considerable impact on people in areas where they occur, which range from environmental to social and economic impacts. There is compelling evidence that FAI land deals are not transparent and inclusive, which raises pertinent concerns with respect to participatory rights, access to information, the compatibility of property rights, environmental protection and the protection of the rights and interests of local communities generally, among other issues. The lack of respect for and protection of local communities’ rights and interests during FAI land deals and activities form the crux of this study. In this light, the overall aim of this thesis is to investigate and ascertain how the procedural aspects of a rights-based approach (RBA) could be used to provide adequate protection to local communities’ rights and interests during FAI activities in Cameroon, Uganda and South Africa. The study is premised on the notion of a RBA to FAI governance and captures the procedural aspects of the right to access to information, public participation and the right to access to justice in international, regional, sub-regional and national human rights legal regimes. It is argued that because these rights have the potential to significantly contribute towards the protection of the rights and interests of people that are adversely affected by development activities, their incorporation remains useful and relevant in the FAI context. It is further claimed that the implementation of the procedural RBA in FAI land deals could strengthen the ability and capacity of the state to increase opportunities for more meaningful dialogue with local communities, while concomitantly helping the state to fulfil its international and national obligations as a duty-bearer to respect, protect and fulfil the rights and interests of its people. In addition, procedural rights encompass elements of good governance and democracy and could be used as a necessary and vital tool to prevent a government’s exercise of arbitrary power generally and in the context of development activities. This is predicated on the belief that procedural rights serve inter alia to strengthen democratic structures and processes and to curb corruption and the mismanagement of national resources, and ultimately to promote sustainable development. In this study, it is argued that a RBA generally and its procedural aspects specifically could play an important role in setting the standards and defining the processes that are appropriate to repudiate the unacceptable impacts of FAI and simultaneously address distributive concerns with the hope of promoting and ensuring more responsible and sustainable FAI. Conversely, the absence of such a normative baseline suggests that large-scale land transfer under the guise of FAI practices would endlessly levy an unacceptable toll on the fundamental rights of the vulnerable host population. The first step in this thesis is to analysis the theoretical concepts of governance and good governance in order to establish the eventual objective of what FAI governance and good FAI governance should entail. A further component of the theoretical analysis includes an analysis of a RBA and a RBA to FAI governance. These components are investigated in order to determine a possible solution to the impacts of FAI activities from a rights-based perspective. Second, the thesis investigates and analyses the procedural aspects of a RBA espoused in international, regional and sub-regional legal regimes. It distils generic characteristics and minimum requirements of the RBA for good FAI governance to be used as benchmarks in the context of project development-related activities, including FAI. As benchmarks, the international, regional and sub-regional legal regimes provide minimum criteria to which the legal frameworks of countries must adhere to and conform with. This part also examines the procedural RBA frameworks in Cameroon, Uganda and South Africa and critically evaluates the legal frameworks in these countries against the distilled generic characteristics and minimum requirements of the RBA in terms of good FAI governance. Third, the thesis concludes with a set of recommendations on the procedural RBA frameworks in Cameroon, Uganda and South Africa. These recommendations are meant to address the current lacunae in these domestic procedural RBA frameworks, and to propose measures designed to enable a situation where the rights and interests of local communities are better protected in the event that FAI land deals are concluded.
Keywords: ACCESS TO INFORMATION; ACCESS TO JUSTICE; Foreign agro-investment; Good governance; Land grabbing; Procedural rights; Public participation; Rights-based approach

Foreign Direct Investments and Economic Growth of African Regions: A Comparative Study - Igbinosa, Sunday O.; Ikponmwosa, Noruwa Abu (UNILAG Journal of Humanities, 2016)
The paper examines the impact of Foreign Direct Investments (FDIs)on economic growth in the five regions of Africa, as well as identifies their respective drivers of growth. It employs the Ordinary Least Squares (OLS) multiple regression analysis to examine the relative impact of Foreign Direct Investments, balance of payments, trade openness, technology and quality of labour force on economic growth in each of the five regions between 1980 and 2012. The study finds that foreign Direct Investments (FDIs) have no significant impact on economic growth in the five regions of Africa. The impact of FDI on growth is positive in Eastern, Middle and Western Africa but negative in Northern and Southern Africa. Similarly, there are differentials in the drivers of growth in the five regions. While trade openness is a negative driver of growth in all regions of Africa except in Northern Africa, both balance of payments and quality of labour force have mixed impacts on economic growth in Africa. In addition, technological progress impacted growth in Middle, Southern Africa and Western Africa but it appears that lack of it retarded growth in Eastern and Northern Africa. The study calls for policy reform frameworks that encourage and boost foreign Direct Investment flows to all regions of Africa, particularly Direct Investments in critical sectors of the economies, as well as check the negative effects of foreign Direct Investments. Furthermore, it recommends that regional economic blocks in Africa should be resuscitated and supported to develop and promote intra-Africa trade and Investments.
Keywords: African regions; Drivers of growth; Economic growth; FDI; Foreign direct investment; Investments